2008
DOI: 10.1093/rheumatology/kem315
|View full text |Cite
|
Sign up to set email alerts
|

MRI changes in psoriatic dactylitis extent of pathology, relationship to tenderness and correlation with clinical indices

Abstract: MRI images demonstrate widespread abnormalities in digits of people with psoriatic arthritis. Tender dactylitic digits have more abnormalities than other digits but the relationship between clinical and MRI scores is not strong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 12 publications
3
77
0
4
Order By: Relevance
“…Recently, it has been reported that typical PsA clinical phenotypes such as distal interphalangeal joint involvement and dactylitis are related to an entheseal-and bone-based pathology, suggesting that the pathogenesis of PsA may be related to the enthesis organ concept (3,18). Extensive bone oedema was found in only 20% of the PsA patients in our cohort, and although in general this was more extensive than in the RA patients, it was not sufficiently common to be used as a diagnostic test.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been reported that typical PsA clinical phenotypes such as distal interphalangeal joint involvement and dactylitis are related to an entheseal-and bone-based pathology, suggesting that the pathogenesis of PsA may be related to the enthesis organ concept (3,18). Extensive bone oedema was found in only 20% of the PsA patients in our cohort, and although in general this was more extensive than in the RA patients, it was not sufficiently common to be used as a diagnostic test.…”
Section: Discussionmentioning
confidence: 99%
“…The Journal of on May 10, 2018 -Published by www.jrheum.org Downloaded from in dactylitis, and is directly linked to microenthesitis 12,13,14 . When compared with RA, tenosynovitis is seen more frequently in PsA, and where flexor tenosynovitis is more common than the extensor counterpart 15,16,17 .…”
Section: Rheumatologymentioning
confidence: 99%
“…91 In another 6-month follow-up study of psoriatic dactylitis, both clinical and MRI improvements were found, but the relationship between clinical and MRI scores was weak. 92 MRI allows quantitative (contrast uptake rate), qualitative (presence/absence), and semiquantitative (scoring) evaluation of joint disease. The OMERACT MRI in Arthritis Working Group has developed an MRI scoring system for peripheral PsA in the hand, and, recently, the forefoot: the PsA MRI Scoring system (PsAMRIS), using the RA MRI Scoring system RAMRIS as template.…”
Section: Mri For Monitoring Peripheral Psoriatic Arthritismentioning
confidence: 99%